KEANEKARAGAMAN DAN KEKERABATAN LALAT BUAH (DIPTERA: TEPHRITIDAE) DI KALIMANTAN SELATAN BERDASARKAN KARAKTER MORFOLOGI DAN MOLEKULAR (RAPD-PCR DAN SEKUENSING DNA) - M Indar Pramudi; Retno Dyah Puspitarini; Bambang Tri Rahardjo (Jurnal Hama dan Penyakit Tumbuhan Tropika, 2013)
Diversity and phylogeny of fruit fly (Diptera: Tephritidae) in South Kalimantan based on morphology and molecular (RAPD-PCR and DNA sequencing). Seven species of fruit fly was known by morphological identification. The fruit flies were found from trapping with methyl eugenol and fruit collecting at all study sites in South Kalimantan. The results showed that as much as 17 plants were infected by fruit fly. Dendrogram based on morphological identification analyzed by using UPGMA with MEGA 4 program consisted in a group consisting of 5 sub-groups. Bactrocera carambolae and Bactrocera papayae of morphology were still a closely related fruit fly at 0.935. Whereas, based on RAPD result analized by UPGMA using 20 character of DNA based, showed that out of seven species consisted 2 groups, 1st group were B. umbrosa, B. occipitalis and sub-group of B. latifrons. The second group consists of sub-groups B.carambolae, B. papaya, sub-group B. albistrigata and B. cucurbitae. The results of dendrogram from sequencing DNA fruit fly analysis comprised one of group and three sub-groups. The first sub-groups were B. papayae, B. carambolae, B. occipitalis, B.latifrons. The second subgroup were B. cucurbitae and B. umbrosa. While B. albistrigata separate but still one group with another fruit flies. The results of DNA sequencing showed that there were a homology of the seven species of the fruit fly i.e at 83 base pair / bp (C), 101 bp (T), 265 bp (G), 420 bp (A), 432 bp (T), 600 bp (A ). The length of the base pair for B. occipitalis, B. cucurbitae, B. albistrigata, B. carambolae, B. papayae, B. latifrons were respectively 615, 898, 570.969, 898 and 615 bp. The results of morphological analysis and RAPD methods showed difference in the distribution of groups and sub-groups. But based on morphologycal and DNA identification seven species of fruit flies found were all same as the genebank.